Synthesis, characterization and toxicity of Cu(II) complexes with metformin Schiff-bases. Issue 2 (3rd April 2017) - Mahmoud, Marwa A.; Ammar, Alaa A.; Sallam, Shehab A.
Abstract : ABSTRACT: Copper complexes of Schiff-bases of metformin with each of salicylaldehyde (HL 1 ); 2, 3-dihydroxybenzaldehyde (H2 L 2 ); 2, 4-dihydroxybenzaldehyde (H2 L 3 ); 2, 5-dihydroxybenzaldehyde (H2 L 4 ); 3, 4-dihydroxybenzaldehyde (H2 L 5 ) and o-hydroxynaphthaldehyde (HL 6 ) were synthesized by template reaction. The new compounds are characterized through elemental analysis, conductivity measurements, magnetic moment, IR, UV–Vis, NMR, ESR, Mass spectroscopy, TEM and molecular modeling. The complexes have square pyramidal structure with magnetic moment values of 1.96–1.81 B.M. and d x 2 − y 2 ground state. TGA, DTG and DTA analysis confirm the proposed stereochemistry. Thermodynamic parameters are calculated for the second and third decomposition steps. The complexes [CuL 1 (H2 O)2 ].2H2 O, [CuL 4 (H2 O)2 ].2H2 O and [CuL 5 OH(H2 O)2 ].3H2 O are evaluated for their hypoglycemic activity in alloxan-induced diabetic mice and have shown toxicity at doses of 20 and 40 mg/kg.